COMMUNICATION PATTERN AND FAMILY TYPOLOGY OF HIGH SCHOOL ADOLESCENTS IN BOGOR - WEST JAVA - Firdanianty Pramono; Djuara P Lubis; Herien Puspitawati; Djoko Susanto (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2017)
Family communication does not occur randomly, but it patterns based on a particular scheme through two communication behavior: conversation and conformity orientations. Te purpose of this study is to analyze communication pattern and family typology of the senior high schools’ students (adolescents) in Bogor – West Java. The research was conducted by survey at six senior high schools in Bogor. Total of respondents were 372 students, consisting of 206 females and 166 males ranging aged between 15-18 years old. Te result are 50.5% with high category of the orientation conversation and 49.5% in low category. In conformity orientation, most of the teenagers (73.7%) have been as high categories and 26.3% in low categories. Te study has also organized in four types of families: 46.2% of consensual (high both in conversation and conformity level), 4.3% of pluralist (high in conversation but low in conformity level), 27.4% of protective (low in conversation but high in conformity level) and 22.0% of non-interventionist (laissez faire) (low in conversational and conformity level). Based on gender, females have often more conversations with family with a higher conformity than males.